Dynamic Modelling of Energy and Growth in South Asia (The Pakistan Development Review, 2007)
Energy plays an important role on the demand and the supply sides of the economy. On the demand side, energy is one of the products a consumer decides to buy to maximise his utility. On the supply side, energy is the key factor of production in addition to labour, capital and other raw materials. Energy is considered to be the key element in the socio-economic development of a country. It also helps to improve the living standards of the society through the increase in economic growth. This implies that there is a causal link running from energy consumption to economic growth. If causality runs from energy consumption to GDP then it implies that an economy is energy dependent and hence energy is a stimulus to economic growth [Jumbe (2004)]. Shortage of energy may negatively affect economic growth and may cause poor economic performance leading to a reduction of income and employment. On the other hand, if causality runs from GDP to energy consumption, this implies that economy is not energy dependent, and hence energy conservation policies may be implemented without adverse effects on economic growth and employment [Masih and Masih (1997)]. If there is no causality between energy consumption and GDP, it implies that energy conservation policies may be pursued without affecting the economy [Jumbe (2004)]. Based on these arguments, it is necessary to analyse the link between energy consumption and economic growth because it is often argued that the increased availability of energy services act as key stimulus of the process of economic development.